Central nucleus of the amygdala as a common substrate of the incubation of drug and natural reinforcer seeking. (8th January 2019) - Roura‐Martínez, David; Ucha, Marcos; Orihuel, Javier; Ballesteros‐Yáñez, Inmaculada; Castillo, Carlos Alberto; Marcos, Alberto; Ambrosio, Emilio; Higuera‐Matas, Alejandro
Abstract: Relapse into drug use is a major problem faced by recovering addicts. In humans, an intensification of the desire for the drug induced by environmental cues—incubation of drug craving—has been observed. In rodents, this phenomenon has been modeled by studying drug seeking under extinction after different times of drug withdrawal (or using a natural reinforcer). Although much progress has been made, an integrated approach simultaneously studying different drug classes and natural reward and examining different brain regions is lacking. Lewis rats were used to study the effects of cocaine, heroin, and sucrose seeking incubation on six key brain regions: the nucleus accumbens shell/core, central/basolateral amygdala, and dorsomedial/ventromedial prefrontal cortex. We analyzed PSD95 and gephyrin protein levels, gene expression of glutamatergic, GABAergic and endocannabinoid elements, and amino acid transmitter levels. The relationships between the areas studied were examined by Structural Equation Modelling. Pathways from medial prefrontal cortex and basolateral complex of the amygdala to central nucleus of the amygdala, but not to the nucleus accumbens, were identified as common elements involved in the incubation phenomenon for different substances. These results suggest a key role for the central nucleus of amygdala and its cortical and amygdalar afferences in the incubation phenomenon, and we suggest that by virtue of its regulatory effects on glutamatergic and GABAergic dynamics within amygdalar circuits, the endocannabinoid system might be a potential target to develop medications that are effective in the context of relapse. Abstract : The incubation of craving has been reported for several drugs of abuse in human subjects. However, the vast majority of basic research has focused on cocaine. Here, we aimed at finding common alterations for cocaine, heroin, and sucrose. Although the incubation of seeking develops with little overlap between reinforcers/drugs, the central nucleus of amygdala emerges as a common hub that agglutinates the influences of the basolateral amygdala and/or dorsomedial prefrontal cortex.